Agglomeration Economies in Semi-industrialized countries: Evidence from Argentina - Borello, Jose Antonio (2011)
This paper identifies and problematizes three gaps in the existing literature on agglomeration economies. First, it argues that the ontology of agglomeration economies, the way in which these economies are conceptualized, needs to be revised. Far from being something “in the air” for all firms to profit from them, tapping these economies requires a conscious and sustained effort from firms. Second, it takes issue with the idea that the functioning of agglomeration economies in semi-industrialized countries can be read of simply from the experience of industrialized ones. Third, the paper challenges current ideas on the geographical extent of urbanization and localization economies within a metropolitan area. The empirical evidence gathered from a detailed survey of 134 firms manufacturing firms in the automotive and steel sectors located in the Buenos Aires Metropolitan Region (BAMR, includes the city proper and the surrounding suburbs) allows us to conclude that localization economies are not necessarily confined to neighbourhoods.